A mixed methods study of emotional exhaustion: Energizing and depleting work within an innovative healthcare team. Issue 6 (2nd November 2017) - Cain, Cindy L.; Taborda-Whitt, Caitlin; Frazer, Monica; Schellinger, Sandra; White, Katie M.; Kaasovic, Jason; Nelson, Brenda; Chant, Allison
ABSTRACT: This mixed methods study documents emotional exhaustion experiences among care team members during the development of an innovative team approach for caring for adults with serious illness. A mixed methods study design was employed to examine depleting work experiences that may produce emotional exhaustion, and energizing aspects of the work that may increase meaningfulness of work, thus reducing emotional exhaustion. The population studied included team members involved in care for adults with serious illness (n = 18). Team members were surveyed quarterly over an 18-month period using the Maslach Burnout Inventory (MBI). The MBI measures burnout, defined as the inability to continue work because of the interactional toll of the work. Analyses of MBI data show that although overall levels of burnout are low, 89% of team members reported moderate/high levels of emotional exhaustion during at least one survey period. In order to understand the kinds of work experiences that may produce or ameliorate emotional exhaustion, qualitative interviews were also conducted with team members at the end of the 18-month period. Major qualitative findings indicate that disputes within the team, environmental pressures, and standardisation of meaningful work leave team members feeling depleted. Having authentic relationships with patients, working as a team, believing in the care model, and practicing autonomy and creativity help team members to restore their emotional energy. Supports for team members' well-being are critical for continued innovation. We conclude with recommendations for improving team members' well-being.